2010
DOI: 10.1016/j.virol.2009.10.013
|View full text |Cite
|
Sign up to set email alerts
|

IFN-α expression and antiviral effects are subtype and cell type specific in the cardiac response to viral infection

Abstract: The interferon-β (IFN-β) response is critical for protection against viral myocarditis in several mouse models, and IFN-α or -β treatment is beneficial against human viral myocarditis. The IFN-β response in cardiac myocytes and cardiac fibroblasts forms an integrated network for organ protection, however the different IFN-α subtypes have not been studied in cardiac cells. We developed a quantitative RT-PCR assay that distinguishes between thirteen highly conserved IFN-α subtypes, and found that reovirus T3D in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 64 publications
5
28
0
Order By: Relevance
“…These proposals are consistent with our current understanding of T1IFN production by cardiomyocytes. Cardiac cells express several of the IFN-␣ subtypes, and the expression pattern varies in a cell-specific manner (89). IRF7, too, is expressed, at a low level, in resting cardiomyocytes, along with additional interferon-stimulated genes (ISGs) and even a low level of IFN-␤ (86); indeed, it has been proposed that the constitutive expression of these proteins renders the cardiomyocytes poised to respond to virus infection, perhaps to protect against the death of these hard-to-replace cells (86).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proposals are consistent with our current understanding of T1IFN production by cardiomyocytes. Cardiac cells express several of the IFN-␣ subtypes, and the expression pattern varies in a cell-specific manner (89). IRF7, too, is expressed, at a low level, in resting cardiomyocytes, along with additional interferon-stimulated genes (ISGs) and even a low level of IFN-␤ (86); indeed, it has been proposed that the constitutive expression of these proteins renders the cardiomyocytes poised to respond to virus infection, perhaps to protect against the death of these hard-to-replace cells (86).…”
Section: Discussionmentioning
confidence: 99%
“…IRF7, too, is expressed, at a low level, in resting cardiomyocytes, along with additional interferon-stimulated genes (ISGs) and even a low level of IFN-␤ (86); indeed, it has been proposed that the constitutive expression of these proteins renders the cardiomyocytes poised to respond to virus infection, perhaps to protect against the death of these hard-to-replace cells (86). Furthermore, T1IFN expression is upregulated in neonatal cardiomyocytes within 8 h of in vitro reovirus infection (89). In addition, elegant work from the Vallejo group has shown that cardiomyocyte-specific in vivo overexpression of TRIF and MDA5, which are important for triggering T1IFN synthesis, confers a substantial degree of protection against the picornavirus encephalomyocarditis virus, limiting both cardiac titers and myocarditis (90,91).…”
Section: Discussionmentioning
confidence: 99%
“…This idea has been supported by the fact that stimulating human leukocytes with agonists for TLR3, -7, -8, and -9 resulted in different IFN-␣ subtype patterns (11,12). Furthermore, different type I IFN subtype profiles can also be induced in a cell-type-specific manner (26), as different cell types express varying levels of both PRRs and transcription factors that can affect subtype promoter regulation. Our present study, however, presents the novel finding that the same virus can induce different type I IFN profiles in the same cell type, depending on the MOI used to infect the cells.…”
Section: Discussionmentioning
confidence: 97%
“…Baig and Fish (4) demonstrated that murine IFN expression profiles differed according to whether the IFN was expressed by lung fibroblast cell lines or tissue stimulated in vivo. Similarly, murine cardiac myocytes and fibroblasts were reported to express different IFNa subtypes in response to reovirus (22). On the other hand, a study of Easlick and coworkers (9) demonstrated that relative IFN-a expression patterns are identical irrespective of the cellular background.…”
Section: Discussionmentioning
confidence: 99%